Squamous Cell Carcinoma over Cutaneous Verrucous Lichen: One Case in Parakou (Benin) - Koudoukpo, Christiane; AKPADJAN, GBEMAWONMEDE FABRICE (My University, 2019)
Abstract Introduction: We report an unusual case of squamous cell carcinoma on a verrucous lichen of chronic evolution taken in charge in Borgou/Alibori UHC in Parakou (Bénin). Observation: A 75-year old Beninese woman with a history of portal hypertension post-viral cirrhosis C treated with negative viral load, had consulted for a large chronic ulceration of the right foot back. The beginning of the symptomatology would go back to about 30 years, marked by lichenified, pruriginous popular lesions; these lesions would initially be treated as eczema and then mycosis by health personnel not specialised in dermatology and multitreated with unspecified topicals. General state was altered. In addition to ulceration, the dermatological examination found plates of hyperpigmented lichen lesion, homogeneous and well limited bilateral and symmetrical topography on the pelvic limbs making difficult to walk. Anatomopathological examination of the biopsy sample straddling the ulceration and its edges suggested a hypertrophic cutaneous lichen associated with keratinizing, infiltrating epidermal carcinoma. The chest-abdominal-pelvic scan showed no metastasis. A complete amputation of the right leg and knee was performed after a psychological interview. The follow-up was marked by an over-infection of the amputation stump by Escherichia coli , which was successfully treated. Healed, she is waiting for orthopedic equipment and possible chemotherapy. Conclusion: This clinical case indicates the need for adequate management of certain potentially precancerous dermatoses, in order to limit the progression to carcinogenic transformation.
Keywords: Cutaneous Verrucous Lichen; Squamous Cell Carcinoma; Amputation; Parakou